Exploring associations between gaze patterns and putative human mirror neuron system activity - Donaldson, Peter H.; Gurvich, Caroline; Fielding, Joanne; Enticott, Peter G. (Frontiers in Human Neuroscience, 2015)
The human mirror neuron system (MNS) is hypothesised to be crucial to social cognition. Given that key MNS-input regions such as the superior temporal sulcus are involved in biological motion processing, and mirror neuron activity in monkeys has been shown to vary with visual attention, aberrant MNS function may be partly attributable to atypical visual input. To examine the relationship between gaze pattern and interpersonal motor resonance (IMR; an index of putative MNS activity), healthy right-handed participants aged 18-40 (n = 26) viewed videos of transitive grasping actions or static hands, whilst the left primary motor cortex received transcranial magnetic stimulation (TMS). Motor-evoked potentials (MEPs) recorded in contralateral hand muscles were used to determine IMR. Participants also underwent eyetracking analysis to assess gaze patterns whilst viewing the same videos. No relationship was observed between predictive gaze (PG) and IMR. However, IMR was positively associated with fixation counts in areas of biological motion in the videos, and negatively associated with object areas. These findings are discussed with reference to visual influences on the MNS, and the possibility that MNS atypicalities might be influenced by visual processes such as aberrant gaze pattern.